2013
DOI: 10.7763/ijbbb.2013.v3.155
|View full text |Cite
|
Sign up to set email alerts
|

Recall Knowledge of Biochemistry for Interns after Graduation from Medical Schools

Abstract: Abstract-New medical graduates were recruited during their internship programme from 10 teaching hospitals for a cross-sectional study, carried out in Riyadh area, Kingdom of Saudi Arabia. A total of 200 participants were included in the study. All the participants filled out the study questionnaire. The questionnaire contained 10 basic Biochemistry questions that the graduates were supposed to recall answers for those questions from their prior knowledge. Other information included were gender, medical school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This reflects the conscious realization of our senior students regarding this problem. These findings are consistent with those of previous studies, which had reported significant knowledge loss and difficulty in retention of anatomy and basic sciences knowledge taught during the preclinical phase [4,5,14,21]. Knowledge loss could be attributed to many reasons including volume overload, teaching methods, lack of clinical application, insufficient time allocated for teaching the subject, in addition to lack of knowledge reinforcement over time [4,5,22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This reflects the conscious realization of our senior students regarding this problem. These findings are consistent with those of previous studies, which had reported significant knowledge loss and difficulty in retention of anatomy and basic sciences knowledge taught during the preclinical phase [4,5,14,21]. Knowledge loss could be attributed to many reasons including volume overload, teaching methods, lack of clinical application, insufficient time allocated for teaching the subject, in addition to lack of knowledge reinforcement over time [4,5,22].…”
Section: Discussionsupporting
confidence: 90%
“…In Saudi Arabia, the majority of medical schools are planning to shift from traditional curricula to more innovative ones; almost all new medical colleges in the kingdom of Saudi Arabia are adopting the hybrid problem-based learning (PBL) curricula [11,12]. Saudi Arabia and other Gulf States' universities in Gulf Corporation regions aimed at reforming their medical curricula based on the outcome of different studies investigating curricular diseases, in addition to students' feedback on basic medical sciences [4,13,14]. Results of some national studies demonstrated that the majority of students found anatomy taught in the traditional, non PBL curricula was irrelevant to their clinical practice, and most of them are unable to recall information taught during the preclinical phase [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There is no significant correlation with score in gender, training rotation, preparation for examinations, and time since graduation. However, there is significant correlation with score in teaching method delivered by their schools of graduation with value of 0.006 [17].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not observed when testing for other basic fields. 4 , 14 , 15 The only probable reason to explain the better performance of interns from private colleges is that is that their entrance qualification for medical schools was foreign secondary schools’ certificates (eg, General Certificate of Education Advanced level and Scholastic Assessment Test). This means that they are more familiar with English as a language of instruction than interns from governmental universities prior to enrolling in the medical schools.…”
Section: Discussionmentioning
confidence: 99%